Sunshine Super Girl The Evonne Goolagong Story. - James, Andrea (Currency plays., 2021)
A grimy old ball, a racquet made from a wooden fruit box, a pair of borrowed shoes ... then the world at her feet. This is the heart-warming story of how Evonne Goolagong Cawley--our Evonne--rose from humble beginnings in an outback farming town to become a world-champion tennis player by the age of just 19.